The Effect of Compensation on the Performance of Automotive Company Sales Division Employees: The Role of Work Discipline as a Mediator - Sugiharjo, R. Joko; Purbasari, Rr Niken; Rahmat, Abdul; Paijan, Paijan (Dinasti Publisher, 2024)
The growth of the automotive industry has a significant role in encouraging economic growth through empowering Human Resources (HR) which contributes to driving a productive economy. Managing the performance of automotive company HR or employees is an important aspect for management to maintain the company’s sustainable success. This research was conducted to determine the effect of compensation and work discipline on the performance of company sales division employees in one of the well-known automotive industries in Jakarta. Researchers used SEM (Structural Equation Modeling) analysis to predict the effect of compensation and work discipline on employee performance, using a quantitative descriptive and causal approach. Random sampling technique was used with a sample size of 108 sales division employees. The results of this research are that compensation has a negative and insignificant effect on employee performance, while compensation has a positive and significant effect on work discipline and work discipline has a positive and significant effect on employee performance. Apart from that, work discipline positively and significantly mediates between compensation and employee performance.